Bram Stoker's Dracula [videorecording (DVD)] - Coppola, Francis Ford, 1939-; Coppola, Francis Ford, 1939-; Fuchs, Fred (Fred S.); Mulvehill, Charles; Hart, James V.; Oldman, Gary; Ryder, Winona, 1971-; Hopkins, Anthony, 1937-; Reeves, Keanu; Grant, Richard E., 1957-; Elwes, Cary, 1962-; Campbell, William, 1959-; et al. (Columbia Pictures Industries : Distributed by Sony Pictures Home Entertainment, 2007)
15th-century warrior Vlad goes off the fight the Turks. Upon his return, he finds that his wife Elisabeta, hearing he was dead, has killed herself. Maddened by this injustice, Vlad curses God, and becomes the immortal blood-eating fiend known as Count Dracula--for centuries. When English attorney Jonathan Harker journeys to Dracula's castle, the Count sees a photograph of his fiancée, Mina Murray. Dracula's patience has been rewarded--Elisabeta lives again! The Count goes to dastardly lengths to possess Mina, while her best friend Lucy, Lucy's three suitors, and Prof. Abraham Van Helsing all become entangled by Dracula's quest. The modern age is dawning, even in Transylvania. Will the Count triumph, or be relegated to the past?